2019
DOI: 10.1177/0020852319834721
|View full text |Cite
|
Sign up to set email alerts
|

The financial sustainability of local authorities in England and Spain: a comparative empirical study

Abstract: In recent years, the financial sustainability of local authorities has been recognised as a concept of crucial importance in ensuring that public services may continue to be delivered to future generations. Although many European countries have implemented programmes to enhance their financial sustainability, local authorities are characterised by differing administrative traditions and achieve diverse outcomes in response to the reforms made. Taking a comparative approach, the present study identifies institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…On the one hand, large governments tend to achieve higher financial sustainability due to greater economies of scale and scope [26]. However, population growth could increase the demand for public services and resources [17,37,38]. This fact involves higher expenditures but it does not always involve higher tax collection since an increase in public revenues does not depend only on the population growth, but also on the financial capacity of the population and of the economic activity.…”
Section: Research Hypothesis About Influential Factors On Financial Smentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, large governments tend to achieve higher financial sustainability due to greater economies of scale and scope [26]. However, population growth could increase the demand for public services and resources [17,37,38]. This fact involves higher expenditures but it does not always involve higher tax collection since an increase in public revenues does not depend only on the population growth, but also on the financial capacity of the population and of the economic activity.…”
Section: Research Hypothesis About Influential Factors On Financial Smentioning
confidence: 99%
“…This fact involves higher expenditures but it does not always involve higher tax collection since an increase in public revenues does not depend only on the population growth, but also on the financial capacity of the population and of the economic activity. In fact, prior research has demonstrated that an increase in the population size could affect negatively on the financial sustainability of local governments in different countries [17]. As a result, the population size can have a negative effect on public spending [46] and on public debt [45], since an increase in the population brings an increase in the demand for resources and services [37].…”
Section: Research Hypothesis About Influential Factors On Financial Smentioning
confidence: 99%
See 3 more Smart Citations